GROWTH PERFORMANCE AND ECONOMIC ANALYSIS OF GROWER RABBITS FED GRADED LEVELS OF TIGER NUT RESIDUE - Alfred, A.K.; Danladi, Y.; Oguntoye, M.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This study evaluated the growth performance of grower rabbits fed diets containing graded levels of tiger nut residue (TNR). Thirty rabbits were randomly assigned to five dietary treatments in a Completely Randomized Design (CRD). The diets included 0% (control), 2%, 4%, 6%, and 8% levels of TNR. Data on feed intake, body weight gain, feed conversion ratio, and mortality were collected over an eight-week period and analyzed using ANOVA. Results revealed no significant differences (P>0.05) in final body weight, daily weight gain, feed intake, or feed conversion ratio across treatments. Rabbits fed diets containing TNR performed comparably to those on the control diet, indicating that inclusion up to 8% does not adversely affect growth performance. Feed cost per kilogram showed a progressive reduction with increasing levels of tiger nut residue inclusion. T1 (control) had the highest feed cost at N173.56/kg, while 8% showed the lowest cost at N159.68/kg. 8% showed the most favorable result with N800.78/kg gain, representing the lowest cost per unit of weight gain. This was followed by T4 (N870.13/kg gain) and T1 (N854.45/kg gain). T3 and T2 showed higher costs per kilogram gain at N907.70 and N929.15 respectively. The results suggest that TNR, an agro-industrial byproduct often discarded as waste, can serve as an alternative energy source in rabbit nutrition. Its incorporation has the potential to reduce reliance on costly conventional feedstuffs and contribute to more sustainable livestock production.